Breast Cancer Knowledge, Attitude and Practice among Metro Women of India Using Social Media: A Cross-Sectional Study - Nibha, Sinha; Alka, Sharma (Current Women's Health Reviews, 2024)
Background: In recent times, social media has been playing an important role in spreading health awareness including breast cancer awareness. Breast cancer is the most common form of cancer among Indian women. Awareness of its risk factors, symptoms, screening methods and positive attitude towards screening and practices are essential to reduce the advanced stage diagnosis and further its mortality rate. This study aims to evaluate knowledge, attitude, and practice about breast cancer in social media users’ in women in the metro city Delhi of India. Methods: We conducted a cross-sectional study from June to December 2019, obtaining data from 397 women using a structured questionnaire. It had four sections that included the socio-demographic profile, knowledge of the risk factors of breast cancer, symptoms and screening, attitude towards screening methods, and its practice to prevent the disease. Results: The mean age of the respondents was 39.34 (±10.22) years. Interestingly, while 92.4% (367/397) knew about the dreaded disease, only 74% knew about its risk factors. The participants who were married, educated and working had reported significantly higher knowledge scores (p ≤ 0.001) Almost three fourth of these women did have a positive attitude towards breast self-examination and clinical examination, and 58% of them were practicing breast self-examination, on monthly basis. Conclusion: Our study findings revealed that women using social media were having a good awareness of risk factors, symptoms, and screening methods. They also have a positive attitude toward screening methods for breast cancer. It highlights the need for awareness generation for practicing early screening behavior.
Keywords: risk factors